Fatigue fracture behavior of Ti-6Al-4V PVD coated - Pitanga Costa, Midori Yoshikawa [UNESP]; Hilario Cioffi, Maria Odila [UNESP]; Rossignolo Venditti, Marcelo Lima [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP] (Elsevier B.V., 2010)
Fatigue, corrosion and wear resistance are important parameters in aircraft components development as landing gear. High strength/weight ratio and effective corrosion resistance make of titanium alloys an alternative choice to replace steel and aluminum alloys. However, titanium alloys have poor tribological properties, which reduce devices performance under friction. PVD coatings tribological systems has been increased due to their attractive mechanical properties as low environmental impact, low friction coefficient, low wear rate and hardness up to 2000 HV.In this study the influence of TiN deposited by PVD on the fatigue strength of Ti-6Al-4V alloy was evaluated. Comparison of fatigue strength of coated specimens and base material shows also a decrease when parts are coated. It was observed that the influence is more significant in high cycle fatigue tests. Scanning electron microscopy technique (SEM) was used to observe crack origin sites and fracture features. (C) 2010 Published by Elsevier Ltd.
Keywords: Fatigue; PVD; Ti-6Al-4V